2020
DOI: 10.1186/s13018-020-01640-7
|View full text |Cite
|
Sign up to set email alerts
|

Valgus stability is enhanced by flexor digitorum superficialis muscle contraction of the index and middle fingers

Abstract: Background: Flexor digitorum superficialis (FDS) muscle provides dynamic stabilization and medial elbow support for ulnar collateral ligament (UCL). The FDS contraction significantly affects the medial joint distance (MJD) through grip contraction. However, it remains unclear whether FDS activity alone contributes to medial elbow stability, or together with the activation of the flexor digitorum profundus during grip contraction, and which finger's FDS is the main contributor to elbow stability. We investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“… 21 A previous study reported that injury care programs should incorporate FDS exercises of these fingers because they, particularly the index and middle fingers, contribute the most to stabilization against valgus stress. 13 However, considering the origin structure of the FDS 21 and the results of the present study, from the viewpoint of transmitting muscle force to the ACT and PCT, it appears necessary to perform exercises for all digits of the FDS in a well-balanced manner, rather than specific finger exercises.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“… 21 A previous study reported that injury care programs should incorporate FDS exercises of these fingers because they, particularly the index and middle fingers, contribute the most to stabilization against valgus stress. 13 However, considering the origin structure of the FDS 21 and the results of the present study, from the viewpoint of transmitting muscle force to the ACT and PCT, it appears necessary to perform exercises for all digits of the FDS in a well-balanced manner, rather than specific finger exercises.…”
Section: Discussionmentioning
confidence: 74%
“… 4 UCL injury is thought to occur as a result of repeated elbow valgus stress. 15 In anatomical studies, 5 , 8 , 21 , 23 biomechanical studies, 1 , 9 , 20 , 24 , 30 and studies using ultrasonography, 13 , 25 the forearm flexors have been found to be important for reducing elbow valgus stress on the UCL. In particular, the flexor digitorum superficialis (FDS) muscle has been reported to be the most important of the forearm flexors for reducing elbow valgus stress on the UCL.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hoshika et al supported this hypothesis and further suggested that valgus stability of the elbows was enhanced by contraction of the flexor digitorum superficialis, especially of the index and middle finger parts of this muscle as revealed by ultrasonography. 13 These findings suggest that the native UCL is an important structure for the dynamic stability of the medial elbow, and its stability should be restored. Further studies are needed to clarify whether this technique has any advantage over traditional UCL reconstruction procedures.…”
Section: Discussionmentioning
confidence: 88%